Vaccine hesitancy and religiosity in a sample of university students in Venezuela - Gabriel Andrade (Taylor & Francis Group, 2021)
The ongoing humanitarian crisis in Venezuela has made it difficult to satisfactorily manage the COVID-19 pandemic in that nation. A vaccination program has begun, but its pace has been slow, as compared to vaccination in other countries. One considerable obstacle faced by vaccination efforts in Venezuela is vaccine hesitancy. Differences across religious groups regarding vaccine hesitancy in Venezuela have not been sufficiently explored. The present study consists of a sample of 230 university students in Venezuela, assessing their intention to get the COVID-19 vaccine. Their responses are compared across religious affiliations, and correlated with three variables: belief in vaccine conspiracy theories, religiosity, and acceptance of the theory of evolution. Results come out showing that Protestants are the religious group most hesitant to get the COVID-19 vaccine, followed by Catholics and the non-religious. Results also show that vaccine hesitancy is correlated with vaccine conspiracy theories and acceptance of the theory of evolution, but not with religiosity itself.